Impact of varicella vaccination in Argentina: Seroprevalence in children and adults in a pediatric hospital. (April 2022) - Gentile, Angela; del Valle Juarez, María; Lucion, María Florencia; Pejito, María Natalia; Martínez, Ana Clara; Folino, Agostina; Viegas, Mariana; Giglio, Norberto
Abstract: Background: Varicella is the primary infection caused by varicella-zoster virus (VZV). In Argentina, the varicella vaccine was introduced in the National Immunization Programme in 2015 as a single dose scheduled at 15 months of age. Objectives: To estimate VZV seroprevalence in a healthy hospital based population before and after vaccine introduction to the NIP. Material y Methods: Cross-sectional, observational, analytic study. Healthy subjects 1–40 years of age were included between June and December 2019 and tested for VZV-antibodies. Results were compared to data from a similar prevaccination study. Results: Out of 599 samples, 11 indeterminate results were excluded, 424 were positive; overall seroprevalence rate was 72.1% (95 %CI = 68, 3–75, 8%). No differences were observed between pre and post vaccination studies for overall prevalence or between age groups, except for vaccinated children aged 11–15 (p = 0, 005). Rates increased in both periods in subjects aged 6 years or older. Primary vaccine failures were 21%; in subjects <5 years 83% seropositive cases had been vaccinated, in >5 year-olds >90% seropositive cases were associated with a history of infection (OR: 10, 4; IC95%: 6, 4–16, 8; p < 0, 001) or household contact (OR:4, 8; IC95%: 3, 1–7, 6; p < 0, 001). Vaccination protected against disease (OR: 0.25; 95 %CI: 0.09–0.68; p = 0.004). Conclusion: seroprevalence was high in all age groups except in unvaccinated 12 to 15-month infants. Seropositivity was due to vaccination in 15 months to 5 year-old children and to infection in older children.